2022
DOI: 10.1111/meca.12410
|View full text |Cite
|
Sign up to set email alerts
|

Tax and pollution in a vertically differentiated duopoly: When consumers matter

Abstract: Inspired by the so-called polluter pays principle, environmental taxes can drive a more sustainable European market. However, unilateral mitigation measures can reduce the competitiveness of carbon-intensive industries, thereby inducing relocation. In this paper, we wonder whether a tax can effectively curb emissions without hurting firms. Our analysis's entry point is that the level of emissions in a region is jointly determined by (i) the number of consumers buying dirty goods and (ii) the environmental qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In a companion paper, Ceccantoni et al (2023) showed that, contrary to common wisdom, a carbon tax does not always hurt consumers. In a vertically differentiated duopoly, they analyze a tax determined by the quality gap between variants and the demand for a dirtier product.…”
Section: Unintended Consequences Of Environmental Policies: Tax Versu...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a companion paper, Ceccantoni et al (2023) showed that, contrary to common wisdom, a carbon tax does not always hurt consumers. In a vertically differentiated duopoly, they analyze a tax determined by the quality gap between variants and the demand for a dirtier product.…”
Section: Unintended Consequences Of Environmental Policies: Tax Versu...mentioning
confidence: 99%
“…To the best of our knowledge, only Ceccantoni et al (2023) point out that the impact of a fiscal measure on market equilibrium, when it is endogenously determined, may change with its recipient. Close in spirit to this contribution, we depart from it in two main respects.…”
Section: Introductionmentioning
confidence: 99%
“…Same as Wang (2021b, 2022) As the difference in product quality, consumers in the market will make different choices according to the utility maximization, that is, some consumers choose to buy high-quality products, some consumers choose to buy low-quality products, and the rest choose not to buy products. Same as Hattori and Tanaka (2018) and Ceccantoni et al (2022), we assume that each consumer buys at most one unit of the product. There are two marginal consumers in the market, 𝐴𝐴 𝐴𝐴 and 𝐴𝐴 𝐴𝐴 .…”
Section: Basic Modelmentioning
confidence: 99%
“…Same as Hattori and Tanaka (2018) and Ceccantoni et al. (2022), we assume that each consumer buys at most one unit of the product. There are two marginal consumers in the market, z $z$ and y $y$.…”
Section: Basic Modelmentioning
confidence: 99%